Targeting aid: what the World Bank has (not) achieved - Peter Nunnenkamp (Journal of international Economic Studies, 2002)
In a report presented at the UN Conference on Financing for Development in March 2002, the World Bank claims that the effectiveness of its financial aid has improved substantially by targeting aid at poor developing countries pursuing sound economic policies. This paper argues that the World Bank's success story rests on a weak empirical foundation. The evidence does not support the view that poverty concerns and policy assessments dominated the distribution of World Bank financing in the 1990s. We conclude that the task of improving the allocation of aid is far from being accomplished. Finally, we discuss some implications of our findings for the future role of the World Bank in development financing.
Keywords: F35; 330; financial aid; World Bank; International Development Association; Entwicklungsfinanzierung; Internationale Kreditvergabe; Entwicklungsbank